2017
DOI: 10.1089/thy.2017.0218
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Swedish Patients with Graves' Hyperthyroidism Is Associated with Changes in Acylcarnitine Levels

Abstract: GD and treatment of the disease is associated with pronounced acyl chain length-dependent alterations in acylcarnitine levels. These changes may be impacted by ethnicity and or dietary differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 42 publications
4
26
1
Order By: Relevance
“…The most prominent small-molecule signature characterizing the restoration of euthyroidism after treatment for Graves' disease is a decline in plasma AC levels (Chng et al 2016, Al-Majdoub et al 2017, which is well in line with observations from population-based studies (Jourdan et al 2014, Lange et al 2018). Yet, the quantitative impact of TH on the blood AC profile remains to be established, since observations in a small cohort (N = 12) of hypothyroid and hyperthyroid did not support strong departures in plasma AC levels from healthy controls (Wong et al 2013).…”
Section: Graves' Diseasesupporting
confidence: 74%
See 2 more Smart Citations
“…The most prominent small-molecule signature characterizing the restoration of euthyroidism after treatment for Graves' disease is a decline in plasma AC levels (Chng et al 2016, Al-Majdoub et al 2017, which is well in line with observations from population-based studies (Jourdan et al 2014, Lange et al 2018). Yet, the quantitative impact of TH on the blood AC profile remains to be established, since observations in a small cohort (N = 12) of hypothyroid and hyperthyroid did not support strong departures in plasma AC levels from healthy controls (Wong et al 2013).…”
Section: Graves' Diseasesupporting
confidence: 74%
“…Yet, the quantitative impact of TH on the blood AC profile remains to be established, since observations in a small cohort (N = 12) of hypothyroid and hyperthyroid did not support strong departures in plasma AC levels from healthy controls (Wong et al 2013). However, the studies done by Chng et al (2016)) and Al-Majdoub et al (2017) confirmed previous observations with respect to phenylalanine, tyrosine as well as TCA cycle intermediates. In general, successful restoration of euthyroidism is characterized by a less pronounced utilization of FAs for energy demands.…”
Section: Graves' Diseasementioning
confidence: 56%
See 1 more Smart Citation
“…Based on this observational, secondary analysis of blood samples, we did not find any metabolomic markers that could separate aforementioned thyroid disorders. This is in contrast to other reports showing distinct metabolic profiles between hyperthyroid patients and euthyroid controls on one hand and hyperthyroid patients rendered euthyroid with antithyroid drugs treatment on the other [8][9][10]. One of these publications revealed that during ATD treatment of GD patients over the first 9 months short-chain acylcarnitines increased, whereas intermediate-chain acylcarnitines decreased, and long-chain acylcarnitines remained stable [8].…”
Section: Discussionmentioning
confidence: 59%
“…Some reports have already mapped the metabolic differences of hyperthyroid disorders, especially GD, compared to the metabolome after treatment [8][9][10]. Another study demonstrated alterations of the metabolome in patients with nodular goiters compared to controls [11].…”
Section: Introductionmentioning
confidence: 99%